1989
DOI: 10.1007/bf00178189
|View full text |Cite
|
Sign up to set email alerts
|

Folinic acid modulation of fluorouracil: tissue kinetics of bolus administration

Abstract: Thymidylate synthase (TS) is the enzyme target of 5-fluorouracil (FUra) that recent laboratory and clinical studies with folinic acid (calcium leucovorin) suggest may mediate important antitumor cytotoxicity. Measurement in carcinoma tissue of parameters related to TS inhibition by 5-fluorodeoxyuridylate (FdUMP), by analogy to hormone receptor analysis, should be useful to determine which patients should receive fluoropyrimidine drug therapy and to evaluate folinic acid requirements. Folinic acid is metabolize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Since reports on the intraperitoneal administration of 5-fluorouracil are encouraging, we used this route to administer 5-fluorouracil plus folinic acid. A scheduledependent synergism is achieved by injecting 5-fluorouracil plus folinic acid [1,19]. The adverse effect of postoperative administration of 5-fluorouracil on wound healing has been reported in various studies [1,10,[14][15][16][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Since reports on the intraperitoneal administration of 5-fluorouracil are encouraging, we used this route to administer 5-fluorouracil plus folinic acid. A scheduledependent synergism is achieved by injecting 5-fluorouracil plus folinic acid [1,19]. The adverse effect of postoperative administration of 5-fluorouracil on wound healing has been reported in various studies [1,10,[14][15][16][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the degree of TS inhibition after fluorouracil treatment correlates well with response (Spears et al 1990). The folate concentration in tumour tissue has been shown to be important for the inhibitory effect of the drug on TS (Spears et al 1989). This data will be useful in the development of methods to improve and individualise the treatment of solid tumours with fluorouracil.…”
Section: Fluorouracilmentioning
confidence: 96%
“…The studies of cellular pharmacokinetics and pharmacodynamics meet considerable practical difficulties as surgical biopsies need to be taken before and after administration of the drug (Spears et al 1984). Recently, however, methods for determination ofTS activity and FdUMP and dUMP concentrations from tissue samples have improved since fine needle aspiration techniques have come into use (Spears et al 1989). It has been shown that the degree of TS inhibition after fluorouracil treatment correlates well with response (Spears et al 1990).…”
Section: Fluorouracilmentioning
confidence: 98%
“…infusion of leucovorin (LV) (60 mg m À2 ) was administered. The pharmacokinetical rationale for this sequential treatment is to obtain simultaneous tissue peak concentration of 5-FU and LV (Spears et al, 1989). The 5-FU dose was selected after a pilot study, showing that an i.p.…”
Section: Intraperitoneal Chemotherapymentioning
confidence: 99%